Students’ Perception on Media Used by The Teacher in Teaching English at Jogja International Culinary Academy - Friadiayani, Asyih ((JELE) Journal Of English Language and Education, 2024)
The aim of this study was to find out how students perceived on the media used by the teacher in Teaching English. This study used qualitative study as its methods. Five students from JICA (Jogja International Culinary Academy) took part in this study. Qualitative research methods will be used to examine questions that can best by verbally describing how participants in a study perceive and interpret various aspects of their environment. The data collection was done by using offline interview in the classroom. Based on the analysis, it revealed that according to students’ perception towards media used by the teacher in teaching English, they gave good perception on it because it can help them so much in understanding English.